The effect of generative AI use on doctoral students’ academic research progress: the moderating role of hedonic gratification - Denis Samwel Ringo (Cogent Education)
Anchored in the uses and gratifications theory, this study explored the effect of ChatGPT use (GPU) on the doctoral students’ academic research progress (ARP) and examined the moderating role of hedonic gratification (HEG) in this relationship. While much of the existing research has focused on ChatGPT’s role in areas such as higher education satisfaction, undergraduate academic performance, academic writing, student engagement, and the development of research skills, there remains a significant empirical gap regarding its effect on ARP. To address this gap, the study broadens existing knowledge by investigating ChatGPT’s influence on ARP, thereby contributing to a deeper understanding of its role in enhancing scholarly outcomes. Data were collected from 215 doctoral students in Tanzania and analyzed using the PROCESS macro and confirmatory factor analysis. The findings demonstrate that GPU significantly enhances ARP. Moreover, HEG significantly moderates this relationship, with the positive effect of GPU on ARP intensifying as levels of HEG increase. By doing so, this study enriches the understanding of how ChatGPT’s capabilities influence academic progress in the context of doctoral research and sheds light on their broader implications for enhancing scholarly outcomes. The study recommends cultivating positive user experiences to maximize the academic benefits of ChatGPT and enhance research progress among doctoral students. To ensure effective and responsible use, universities should offer training on ChatGPT’s proper application, focusing on academic integrity and ethical considerations. This will help students viewing the tool as a supplement, rather than a replacement for, critical thinking and intellectual effort.